Analysis of Spar Cap Damage of Wind Turbine Blades and Reliability Verification of Repair Scheme - Xiuhai LI; Jianhui MAO; Chuanlong LUO; Bowen SHI (南方能源建设)
[Objective] Wrinkle is a kind of defect that may occur in the manufacturing process of wind turbine blades. It may cause the strength of the blade to decrease, and in serious cases, cracks will be produced and lead to blade fracture, how to repair the wrinkle defects and verify the structural safety of the blade after repair is the focus of this paper. [Method] The blade of a megawatt-class unit of wind farm with spar cap wrinkling damage was selected as the research object. Firstly, the blade three-dimensional structural model and finite element model were established, and the blade buckling stability and the permissible number of spar cap were analyzed through finite element simulation; then, the wrinkle height was predicted through the strength loss ratio of glass fiber reinforced plastic (FRP), and a repair scheme was formulated; finally, the reliability of the repair scheme was verified through the full-size static and fatigue tests of the blade.[Reslut] The results show that the spar cap would not have buckling instability and fatigue failure if there is no wrinkling defect; the repaired blade passed the static and fatigue tests. [Conclusion] The repair scheme formulated based on the FRP strength loss ratio has a certain degree of reliability and provides a reference for the repair of wind turbine blade spar cap wrinkle.